Avaliação de sintomas ansiosos em mulheres com Transtorno Depressivo Maior no periparto atendidas em um Serviço Universitário de Ginecologia e Obstetrícia - Kyze Lino Quintela (2021)
Pregnancy and puerperium are moments in the lives of some women which may increase vulnerability and susceptibility to the manifestation or resurgence of mental disorders, mostly depressive and anxiety disorders. Such disorders are associated with increased gestational risk and harmful consequences for the pregnant/puerperal woman and their offspring. Some studies have observed a higher prevalence of anxiety signs and symptoms in women who depressed in the perinatal period, which may suggest a clinical distinction between the depressive disorder during this period and the depressive disorder in other phases of a woman's life. This study aims to identify the prevalence of anxiety symptoms in pregnant and postpartum women with perinatal depression who volunteered in a longitudinal study, conducted at Universidade Federal de Minas Gerais (UFMG) over an eleven-year period. The results of the sample analysis suggest that pregnant and postpartum women with positive screening for perinatal depression had more anxiety symptoms compared to their peers who did not have perinatal depression. Given the importance of the theme for health promotion and prevention, broader and more specific studies need to be carried out to better define this condition in order to promote more efficient diagnostic and therapeutic resources.